2021
DOI: 10.3390/cancers13112546
|View full text |Cite
|
Sign up to set email alerts
|

CSF1/CSF1R Axis Blockade Limits Mesothelioma and Enhances Efficiency of Anti-PDL1 Immunotherapy

Abstract: Colony-Stimulating Factor 1 (CSF1)/Colony-Stimulating Factor Receptor 1 (CSF1R) signaling orchestrates tumor-associated macrophage (TAM) recruitment and polarization towards a pro-tumor M2 phenotype, the dominant phenotype of TAMs infiltrating mesothelioma tumors. We hypothesized that CSF1/CSF1R inhibition would halt mesothelioma growth by targeting immunosuppressive M2 macrophages and unleashing efficient T cell responses. We also hypothesized that CSF1/CSF1R blockade would enhance the efficacy of a PDL1 inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…The survival, proliferation and function of TAMs depend to a large extent on CSF-1R signaling ( Figure 4 ). Blocking the CSF-1-CSF-1R axis inhibits the polarization of macrophages, thereby reducing tumor cell proliferation and inducing TAM apoptosis [ 73 ] ( Figure 4 ). Many preclinical studies demonstrated high efficacies of CSF-1R inhibitors.…”
Section: Macrophages In Tumor Therapymentioning
confidence: 99%
“…The survival, proliferation and function of TAMs depend to a large extent on CSF-1R signaling ( Figure 4 ). Blocking the CSF-1-CSF-1R axis inhibits the polarization of macrophages, thereby reducing tumor cell proliferation and inducing TAM apoptosis [ 73 ] ( Figure 4 ). Many preclinical studies demonstrated high efficacies of CSF-1R inhibitors.…”
Section: Macrophages In Tumor Therapymentioning
confidence: 99%
“…Accordingly, in vitro and in vivo studies have demonstrated that inhibition of CSF-1R might restore the CD8 + T cell anti-tumor response [ 98 , 100 ]. Inhibition of CSF-1R not only avoided mesothelioma progression and enhanced T cell response, but was also shown to increase the sensitivity of mesothelioma to PD-L1 inhibitors [ 101 ]. Additionally, in vivo studies have demonstrated the efficacy of a recently developed monoclonal antibody anti-CSF-1R (RG7155) in the reduction of CD68 + /CD163 + TAMs in mesothelioma biopsies [ 102 ].…”
Section: Mesothelioma Microenvironment Crosstalk: Molecular Mechanismsmentioning
confidence: 99%
“…The presence of M-CSF and IL-34 was associated with short survival and chemoresistance [ 98 , 99 ]. Recently, the inhibition of CSF-1R has been shown to reduce mesothelioma progression and increase the susceptibility of MPM to immune checkpoint inhibitors [ 101 ]. The activation of the IL-1β/IL-1R signaling pathway in tumors by TAMs is correlated with the acquisition of a CSC-like phenotype [ 96 ].…”
Section: Mesothelioma Microenvironment Crosstalk: Molecular Mechanismsmentioning
confidence: 99%
“…CSF-1/CSF-1R signaling mediates tumor-associated macrophages recruitment and M2 polarization. In experimental mesotheliomas, combined a highly selective small molecule CSF-1R inhibitor-BLZ945 with an anti-PDL1 agent was more effective in retarding tumor growth compared to each monotherapy 58 . Moreover, AMG 820, an anti-CSF-1R antibody, showed acceptable safety profile in combination with pembrolizumab in adults with advanced solid tumors by reducing CSF-1 dependent CD16 expressing monocytes, and increasing PD-L1 expression and infiltrating T-lymphocyte numbers in advanced solid tumor biopsies 57 .…”
Section: The Relationship Between Csf-1/csf-1r Axis and Tam In Malignant Tumorsmentioning
confidence: 98%
“…However, numerous recent studies have found that CSF-1/CSF-1R axis blockade can improve the efficiency of immune checkpoint inhibitors, especially PD-L1. Thus, in terms of tumor control, the combination therapy targeting CSF-1/CSF-1R axis and immune checkpoint molecular has more reliable efficacy 57 , 58 . CSF-1/CSF-1R signaling mediates tumor-associated macrophages recruitment and M2 polarization.…”
Section: The Relationship Between Csf-1/csf-1r Axis and Tam In Malignant Tumorsmentioning
confidence: 99%